The impact of the Mediterranean diet on gut microbiota in diabesity - Woodard, Claudia (Kansas State University, 2021)
Diabetes and obesity are currently some of the most prevalent chronic conditions and are still growing globally. These conditions are accompanied by modifications in the gut microbiota in connection to specific dietary patterns. This report aims to review the research into the human gut microbiota in connection to the Mediterranean style diet of type 2 diabetes mellitus associated with obesity. Current research has revealed that the gut microbiota differs in lean versus obese people, as well as individuals who have type 2 diabetes and people who do not. To comprehend the change of gut microbiota in obesity and type 2 diabetes, it is important to first understand the mechanisms that regulate the gut microbiota composition. During the early stages of life, several aspects affect the gut microbiome. Some of these aspects include the mode of delivery, if breastfeed or formula-fed, level of prematurity of the child, and antibiotic use. From the time a child is introduced to table foods, the gut microbiome is affected by dietary nutrient composition. There have been new and ongoing research on the role of gut microbiota in obesity and diabetes concerning dietary intake. Results showed that a Western-style diet promotes a gut microbiota which tends to promote obesity, whereas the Mediterranean style diet has beneficial influence on the gut microbiota, so it may be considered for use in clinical management and prevention in diabesity. This could indicate that specific dietary interventions may favorably affect metabolism due to the change in gut microbiota composition. Potential causes of this beneficial effect of the Mediterranean style diet on the gut microbiota in diabetes and obesity has been attributed to an increase in non-digestible dietary fibers resulting in the increased production of short-chain fatty acids through fermentation and increased probiotic intake, leading to an overall reduction in gut dysbiosis with an improvement in insulin resistance. Additionally, some research found a connection between the gut microbiome and the level of activity in the energy and glucose metabolism effect on the endocannabinoid systems. Thus, the purpose of this report is to determine the connection the impact nutritional components of the Mediterranean style diet have on the gut microbiota in individuals with diabesity and to understand and create awareness of the influence the diet has over these possible key components.
Keywords: Mediterranean diet; Type 2 diabetes mellitus; Microbiota